Brugada Syndrome-Associated Genetic Loci Are Associated With J-Point Elevation and an Increased Risk of Cardiac Arrest - Andreasen, Laura; Ghouse, Jonas; Skov, Morten W.; Have, Christian T.; Ahlberg, Gustav; Rasmussen, Peter V.; Linneberg, Allan; Pedersen, Oluf; Platonov, Pyotr G.; Haunsø, Stig; Svendsen, Jesper H.; Hansen, Torben; et al. (Frontiers in Physiology, 2018)
Introduction: A previous genome-wide association study found three genetic loci, rs9388451, rs10428132, and rs11708996, to increase the risk of Brugada Syndrome (BrS). Since the effect of these loci in the general population is unknown, we aimed to investigate the effect on electrocardiogram (ECG) parameters and outcomes in the general population. Material and Methods: A cohort of 6,161 individuals (median age 45 [interquartile range (IQR) 40-50] years, 49% males), with available digital ECGs, was genotyped and subsequently followed for a median period of 13 [IQR 12.6-13.4] years. Data on outcomes were collected from Danish administrative healthcare registries. Furthermore, ~400.000 persons from UK Biobank were investigated for associations between the three loci and cardiac arrest/ventricular fibrillation (VF). Results: Homozygote carriers of the C allele in rs6800541 intronic to SCN10A had a significantly larger J-point elevation (JPE) compared with wildtype carriers (11 V vs 6 V, P<0.001). There was an additive effect of carrying multiple BrS-associated risk alleles with an increased JPE in lead V1.  None of the BrS-associated genetic loci predisposed to syncope, atrial fibrillation, or total mortality in the general population of Denmark. The rs9388451 genetic locus adjacent to the HEY2 gene was associated with cardiac arrest/VF in an analysis using the UK Biobank study (odds ratio=1.13 (95% confidence interval: 1.08-1.18), P=0.006). Conclusions: BrS-associated risk alleles increase the JPE in lead V1 in an additive manner, but was not associated with increased mortality or syncope in the general population of Denmark. However, the HEY2 risk allele increased the risk of cardiac arrest/ VF in the larger population study of UK Biobank indicating an important role of this common genetic locus.